Gambaran Lama Kerja Analgesi Pada Spinal Anestesi Menggunakan Bupivakain 0,5 % Hiperbarik 12,5mg Dengan Tambahan Morfin 0,2 Mg Terhadap Waktu Respon Nyeri Pasien Pasca Sectio Caesarea Di RS Vita Insani - Tri Badi; Sulastri Sulastri; Immanuel Rianto Sitorus (Pusat riset dan Inovasi Nasional, 2022)
The combination of low-dose intrathecal morphine with spinal anesthesia provides an effective and safe postoperative analgesia effect and may enhance the analgesia effect of bupivacaine. At Vita Insani Hospital, almost all patients who will undergo S.C surgery are generally carried out with spinal anesthesia by an anesthesiologist with habitual drug use and the dose used is bupivacaine 0.5% hyperbaric 12.5 mg plus adjuvant morphine 0.2 mg. Seeing the phenomenon of this case, the researcher wanted to see how the description of the effect of giving bupivacaine 0.5% hyperbaric 12.5 mg plus adjuvant morphine 0.2 mg which is commonly used in spinal anesthesia on the duration of analgesia and pain response time that will be felt by patients after sectio caesarea surgery at RS Vita Insani. The research design used is a quantitative descriptive method with a cross sectional approach, with the method used in this research is a prospective descriptive conducted in the post-surgical treatment room (recovery room) Central Surgical Installation (IBS) Vita Insani Hospital from May 2021 to July 2021. This study only uses one group because it only describes the results of a condition. The number of samples as many as 63 samples with purposive sampling technique in accordance with the inclusion and exclusion criteria that have been determined The respondents felt the most pain starting at 3 hours of postoperative assessment with respondents who felt mild pain as many as 31 cases (49.2%) and at least respondents who felt severe pain as many as 5 cases (7.9% ). and pain increased at 4 hours postoperative assessment, namely moderate pain. However, it can also be seen at 0 to 2 hours of postoperative pain assessment that more respondents still do not feel pain. That the duration of analgesia began to decrease in the first hour and then the most significant postoperative pain was felt at 3 hours postoperatively. So that other pain management is needed to reduce the pain experienced by patients such as relaxation techniques, distraction and collaboration of pharmacological therapy in dealing with postoperative pain.